Mental health: current trends in pharmacy and new concepts - N. A. Bilousova; A. V. Kabachna (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The implementation of the National Mental Health Gap Action Program (mhGAP), which aims to broaden the management of patients with mental disorders in primary care, should involve not only primary care physicians but also pharmacists. Pharmacists play a crucial role by providing medications within the expanded Medical Guarantee Program for drug reimbursement in outpatient treatment of mental and behavioral disorders. Additionally, they offer pharmaceutical care for patients dealing with stress disorders and insomnia, adhering to the Good Pharmacy Practice (GPP) standards.